Wavelength assignment in design dwdm transport network using algorithm BCO-RWA - Ageyev, Dmitry; Pereverzev, Alexander (Видавництво Львівської політехніки, 2012)
The main problem in designing DWDM transport networks is the wavelength assignment of light paths. One way of solving this problem is to use the algorithm BCO-RWA. However, BCO-RWA has the following disadvantages: algorithm not solved the problem of choosing the location of the optical convector in the network; base algorithm ignores placement optical convector during calculating route selecting probability; base algorithm do not take into account the nonlinear four-wave mixing phenomenon. In this paper we present an algorithm which takes into account a number of disadvantages due to modifications introduced in the algorithm.
Keywords: BCO-RWA; network; route; light path; connection; DWDM